Overcoming Financial Management Hurdles in Southeast Asian Micro Businesses: Insights from a Literature Review - Makatita, Reyner Frengky (JUSTBEST Journal of Sustainable Business and Management, 2024)
Micro businesses are a vital component of Southeast Asia’s economy, contributing significantly to employment and poverty reduction. However, these businesses face several financial management challenges that hinder their growth and sustainability. This literature review examines the financial management hurdles faced by micro businesses in Southeast Asia, focusing on challenges such as poor financial literacy, limited access to finance, inadequate cash flow management, and the lack of formal financial systems. It also explores potential solutions to these challenges, including improving financial literacy, increasing access to affordable finance, and promoting the use of digital financial tools. While financial management practices vary across countries in Southeast Asia, micro business owners consistently face barriers that limit their ability to manage resources effectively. The review suggests that improving financial literacy through targeted education programs and enhancing access to formal financial services are key to addressing these issues. Additionally, the role of digital technologies in streamlining financial management practices is explored, highlighting the importance of promoting digital inclusion for micro businesses. This review contributes to the understanding of financial management challenges in micro businesses and provides insights for policymakers, financial institutions, and development organizations to support the growth and sustainability of micro enterprises in Southeast Asia.